Facilitating data for decision making to improve Health Management Information Systems reporting at four supported sites in Uganda - Kanakulya, Hassan; Kyozira, Carol; Kaduyu, Paul; Mukisa, Rose (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To share Data for Decision-Making (DDM) initiatives used across health service sites supported by USAID-funded Fistula Care Plus (FC+) Project at EngenderHealth. Methods: FC+ and the HMIS Department at the Ministry of Health conducted a DQA at four supported sites in Jinja, Hoima, Masaka and Kamuli to verify whether reported data was consistent with facility registers. A qualitative assessment identified other data quality/capacity issues. The team worked with facility staff from October 2016 to March 2018 to address data and capacity gaps, including capacity building, feedback through DDM meetings, development of DDM committees, and support to action plans developed during the DQA exercise. Results: 60%-80% of which were implemented. Three sites set programmatic targetsfor2017-2018 and shared them to facilitate better resource allocation. Three sites used data visualization. All sites made critical decisions based on data they generated, such as timely maternal death audits, forecasting and re-supply of HMIS tools. There was improved data accuracy, with scores on indicators of acceptable data quality increasing at Kamuli from 45% to 60%, Jinja from 9% to 33%, Kitovu from 60% to 83%, and Hoima 4 % to 23%. Conclusions: These results demonstrate the value of and effective strategies for promoting pragmatic data use among those who collect clinical data, going beyond the traditional use of data for reporting purposes only.